The Influence of the Liveworksheets-Based Discovery Learning Model on the Critical Thinking Ability of 10th Grade Students in Phase E: . - Armawati, Wella; Bigharta Bekti Susetyo (Global Action and Education for Society, 2025)
Critical thinking skills are essential in Geography learning, requiring analysis of spatial and regional phenomena. However, many students find it difficult to develop these skills due to teaching methods that do not actively engage them. This study aims to analyze the effect of the Discovery Learning model based on Liveworksheets on the critical thinking skills of 10th-grade students in Phase E at SMA Negeri 7 Padang. The method used is quantitative with a quasi-experimental design and a sampling technique of purposive sampling, involving 72 students divided into experimental and control groups. The instrument used consists of 10 essay questions based on Ennis' indicators. The pretest results showed low initial abilities in both classes. The average pretest score for the experimental class was 20.86, and for the control class, it was 19.08. After the treatment, the average posttest score for the experimental class increased to 24.67, while for the control class, it was 19.42. The t-test showed a significance value of 0.000 (< 0.05), indicating a significant difference between the two groups. The N-Gain value for the experimental class was 0.1305 and for the control class was 0.0865, both of which fall into the low category. Nevertheless, the Liveworksheets-based Discovery Learning model proved more effective in improving students' critical thinking skills compared to conventional learning.